Combining household surveys and interviews to understand irrigation technology adoption among farmers in Maharashtra (India) - Anja Šaponjić; Soham Adla; Lisa Scholten; Erik Mostert; Saket Pande (Frontiers in Water)
Farmers in Maharashtra, India, face water scarcity, leading to poor crop yields and farmer indebtedness. To improve water use efficiency and mitigate climate change impacts on livelihoods, governments promote micro-irrigation technologies. Still, the rate of adoption of these technologies remains low. This study aims to develop a complete overview of the socio-economic, psychological and contextual factors that influence adoption in a drought prone region of Maharashtra by combining two well-known models for understanding behavior, the RANAS model and the SSBC model. Our analysis used a mixed method approach. First, a logistic regression was made, using survey data from 419 farming households covering socio-economic and individual-level psychological factors from the RANAS-model. In addition, 22 qualitative semi-structured interviews were held to explore contextual, social, and personal-level factors, using insights from the SSBC model. The results show that farmers who are concerned with the availability of their water source and believe that getting water is becoming more difficult may not adopt micro irrigation systems. Prevalent norms influence farmers actions and choices. Strong financial abilities and technical skills are important drivers of the adoption of micro irrigation systems, in addition to the confidence in their abilities to buy and maintain them. Farmers who adopt micro irrigation systems are often more well-off than farmers adopting furrow irrigation systems and their ability to invest outweighs the importance of saving water through the adoption of efficient micro irrigation systems. Finally, we find that tremendous efforts, high uncertainty of the process of getting a micro-irrigation subsidy, combined with low trust in the government in the area, and feelings of unfairness negatively influence farmers and discourage them to adopt micro-irrigation. Taken together, our mixed-methods approach led to a more nuanced, technology-specific understanding of irrigation technology adoption beyond existing studies, offering valuable insights for designing more effective behavior change strategies and possible ways to encourage the adoption of water efficient irrigation technologies.